Potensi Pariwisata Di Wilayah Pesisir Kabupaten Buleleng, Bali - Retha Pramesti; Danang Agung Indriatno; Muthia Redha Fadhilah; Nanda Athalla Putra; Fadhli Wibisetya Pratama (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2022)
The coastal area is a space that has potential in various aspects. This coastal area is important to be developed both in the renewable and non-renewable natural resources sector. In practice, Indonesia is still considered unable to utilize and manage coastal area resources. As a result, the potentials they have have not been able to provide optimal utilization in regional economic development. The people of Buleleng in the Province of Bali where most of the population are fishermen also feel the same way. Many fishermen live on the poverty line and until now have not been prosperous due to the small income in their daily livelihood. In this study, the data collection method as well as information used the Analytical Hierarchy Process approach based on SWOT analysis (Strength, Weakness, Opportunity, Threat). The results of the study indicate that there is a need for development both in the economic sector of the coastal area and in community development. The strategy that can be used is to increase technology and specialization so that the coastal areas of Buleleng can compete. Keywords: Economic Management; Community Development; Coastal Areas